Penegakan Hukum Keimigrasian Terhadap Warga Negara Asing Yang Menyalahgunakan Izin Tinggal Kunjungan Di Indonesia - Shafina, Lailan; Arif Sahlepi, Muhammad (UIR Press, 2024)
This research examines the enforcement of immigration law against Foreign Nationals (FNs) who abuse their stay permits in Indonesia. However, their presence often involves violations of immigration rules, such as overstaying, which impact immigration regulations and policies. The necessity of internationally based laws to regulate residency becomes crucial in addressing these challenges. While the arrival of FNs can have positive impacts such as increased tourism and investment, there are also risks of negative impacts, including national security and resilience. This study employs a qualitative approach using juridical-normative legal research methods, gathering data through literature studies related to the abuse of stay permits by FNs. The analysis results indicate the need for strict law enforcement through administrative actions, investigation, and prosecution of immigration violations. Despite these efforts being crucial for maintaining national sovereignty, challenges persist such as limited community participation in reporting violations, as well as budgetary and human resource constraints in immigration law enforcement. In conclusion, immigration law enforcement in Indonesia requires strong cross-sectoral coordination, increased public awareness, and reforms in human resource management and budgeting to enhance its effectiveness. These steps are necessary to uphold national sovereignty and ensure justice in immigration law enforcement against FNs in Indonesia.